ONTOLOGY OF LIABILITY OF LEGAL PERSONS - Semykina, Ольга Ивановна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
In the article from the point of view of ontology the approaches of the legislator, legal expert and practice to the legalization of the institution of liability of legal persons in the Russian criminal and criminal procedure law are considered. Thus, the positive experience of reforming Russian law in the XIX century made it possible to analyze the norms of liability of legal persons in the Penal Punishment and Correctional Ordinance Regulations of 1845, to emphasize the procedural features of applying criminal procedural coercive measures to legal persons in the Criminal Procedure Charter of 1864, and also touch on the judicial practice, "graphically" inscribing the use of law enforcement activities precedents of quasi-criminal liability of legal persons. Identified as a result of comparative legal monitoring of the Russian legislation, theory and practice of the XIX – XX centuries factors, that historically determine the legal existence of the institution of liability of legal persons allowed to continue differentiation of the approaches of the legislator and doctrinal research in subsequent periods of development of Russian law. In this part in the article various legislative mechanisms for the recognition of legal persons as predicates of criminal legal relations are highlighted on the 20-80s. XX century. In the continuation actualized the doctrinal points of view "pro et contra", voiced in the science of criminal law in attempts to construct norms on the criminal liability of legal persons in the several drafts of the Criminal Code of the Russian Federation 1996. The article reflects the results of the implementation of the scientific project No. 16-23-08001-OGN / 18 "Criminal and Administrative Liability of Legal Persons for Violation of Competition Rules", which was funded by RFBR and FMSH.